Evaluating the Protective Effectiveness of Rubber Glove Materials Against Organic Solvents Upon Repeated Exposure and Decontamination - Li-Wen Liu; Cheng-Ping Chang; Yu-Wen Lin; Wei-Ming Chu (Elsevier, 2024)
Background: Glove reuse poses risks, as chemicals can persist even after cleaning. Decontamination methods like thermal aeration, recommended by US OSHA, vary in effectiveness. Some studies show promising results, while others emphasize the importance of considering both permeation and tensile strength changes. This research advocates for informed glove reuse, emphasizing optimal thermal aeration temperatures and providing evidence to guide users in maintaining protection efficiency. Methods: The investigation evaluated Neoprene and Nitrile gloves (22 mils). Permeation tests with toluene and acetone adhered to American Society for Testing Materials (ASTM) F739 standards. Decontamination optimization involved aeration at various temperatures. The experiment proceeded with a maximum of 22 re-exposure cycles. Tensile strength and elongation were assessed following ASTM D 412 protocols. Breakthrough time differences were statistically analyzed using t-test and ANOVA. Results: At room temperature, glove residuals decreased, and standardized breakthrough time (SBT)2 was significantly lower than SBT1, indicating reduced protection. Higher temperature decontamination accelerated residual removal, with ΔSBT (SBT2/SBT1) exceeding 100%, signifying restored protection. Tensile tests showed stable neoprene properties postdecontamination. Results underscore thermal aeration's efficacy for gloves reuse, emphasizing temperature's pivotal role. Findings recommend meticulous management strategies, especially post-breakthrough, to uphold glove-protective performance. Conclusions: Thermal aeration at 100°C for 1 hour proves effective, restoring protection without compromising glove strength. The study, covering twenty cycles, suggests safe glove reuse with proper decontamination, reducing costs significantly. However, limitations in chemical-glove combinations and exclusive focus on specific gloves caution against broad generalization. The absence of regulatory directives on glove reuse highlight the importance of informed selection and rigorous decontamination validation for workplace safety practices.